Employee Performance as a Result of Psychological Resources and Perceived Organizational Support in Indonesian Technology Startups - Yeni, Misra; Amran, Amran; Roni, Khairun A; Asman, Muhammad; Girsang, Ronald N; Putra, Rio (Maneggio, 2026)
This study aims to analyze the role of psychological resources (Psychological Capital/PsyCap) and perceived organizational support (Perceived Organizational Support/POS) in explaining employee performance at technology startups in Indonesia. The dynamic, flexible, and digitally collaborative work environment of startups requires employees to not only possess technical skills, but also psychological readiness and adequate organizational support in order to remain productive amid high work pressure. This study uses an explanatory quantitative approach with SEM-PLS analysis of data collected through an online questionnaire from 150 technology startup employees in Indonesia using the Psychological Capital Questionnaire (PCQ), Survey of Perceived Organizational Support (SPOS), and employee performance scales based on task performance and contextual performance.  Validity, reliability, and hypothesis testing were conducted through outer model and inner model evaluation as well as bootstrapping procedures. The analysis results show that POS (β = 0.260; p < 0.05) and PsyCap (β = 0.174; p < 0.05) have a positive and significant effect on employee performance, with POS having a stronger effect than PsyCap. The R² value of 0.130 indicates that the contribution of both variables is at a moderate level, opening up the possibility of other psychological mechanisms such as engagement, readiness for change, motivation, and well-being that have the potential to mediate this relationship. These findings confirm that the performance of technology startup employees in Indonesia is the result of the interaction between external organizational support and internal psychological strengths of individuals, so startup management needs to simultaneously strengthen organizational support and develop employee psychological capital to encourage sustainable performance.